Peningkatan Keaktifan dan Hasil Belajar Bentuk Pangkat, Akar dan Logaritma Menggunakan Make a Match Circle Game - Penni Ratnawati; Wikan Budi Utami (Universitas Sarjanawiyata Tamansiswa, 2021)
The Objective of this research is conducting the learning process by Make a Match Circle Game to increase the activeness and its learning results for exponents, surds and logarithms for their abilities in achieving the minimum competence criteria 75.00, in which the make a match circle game learning process is expected to change the students’ attitude specifically their activeness in learning process. The learning model in this Classroom Action Research is conducted in two cycles and every cycle must involve planning, implementation, observation and game tournament. The subject of this research is Class X of Analysis Chemistry 4 in Vocational High School 1 Temanggung the academic year of 2019/2020. Based on this research which is conducted through observation of initial students ’condition and the results of classroom action research consisting two cycles founded the increase of students’ results in mastering the competences of exponents, surds and logarithms. The increasing of mastering the competences initiated since first cycle in which the average of 61, 43 with 25 % above minimum competence Criteria, and the average of 75, 65 with mastering level 63, 89.